2014
DOI: 10.15405/ejsbs.133
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Barriers to Personal Creativity: Validation of an Inventory Involving High Education Students

Abstract: The topic of creativity in higher education has been increasingly emphasized as support to the social and technological innovation. This study presents the adaptation and validation of the Inventory of Barriers to Personal Creativity (Alencar, 1999) for Portuguese college students. The sample was composed by 582 students from a public university in Northern Portugal, whose ages ranged from 18 to 59 (M=23.41; SD=5.38), belonging to three main domains of graduation courses (Arts and Humanities, Social Sciences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
1
0
11
Order By: Relevance
“…According to Jackson (2006a, b), having sufficient time and space in the curriculum to allow students to develop their own creativity is one of the conditions that appear to facilitate students' creativity. Morais et al (2014a) identified as main lack of time dimension factors: Personal time to explore, to put ideas on practice or develop them, evaluate them. As Blamires and Peterson (2014) recognise, the meaning of creativity is an important aspect that might be understood in terms of classroom practice especially in relation to the concept of assessment for learning.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jackson (2006a, b), having sufficient time and space in the curriculum to allow students to develop their own creativity is one of the conditions that appear to facilitate students' creativity. Morais et al (2014a) identified as main lack of time dimension factors: Personal time to explore, to put ideas on practice or develop them, evaluate them. As Blamires and Peterson (2014) recognise, the meaning of creativity is an important aspect that might be understood in terms of classroom practice especially in relation to the concept of assessment for learning.…”
Section: Discussionmentioning
confidence: 99%
“…Em especial, Martin (1990) demonstrou que várias autopercepções, tais como autoconfiança e autoeficácia criativa, podem ser consideradas como barreiras individuais críticas à criatividade. Além disso, pesquisas anteriores indicaram que certos traços de personalidade, tais como timidez, conservadorismo e inibição podem impedir a expressão criativa dos indivíduos num contexto social como a sala de aula (MORAIS et al, 2014;PUCCIO;GRIVAS, 2009). As barreiras individuais têm sido caracterizadas como os principais fortes impedimentos que podem afetar a motivação criativa (CSIKSZENTMIHALYI, 1990;FILA;PURZER;MATHIS, 2014;HILAL;HUSIN;ZAYED, 2013;INTASAO;HAO, 2018;NORDIN;MALIK, 2015).…”
Section: Introductionunclassified
“…Além das barreiras individuais, vários fatores contextuais têm sido descritos como obstáculos "ambientais" à expressão criativa, tais como falta de recursos, prazos rigorosos, falta de lazer, carga pesada de trabalho e falta de oportunidades de expressão criativa (AMABILE, 1998;CRAFT, 2005;MORAIS et al, 2014;PALETZ, 2012). A repressão social também tem sido relatada como um obstáculo comum à expressão criativa entre os jovens adultos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Contudo, as áreas curriculares estruturam oferta educativa no ensino superior, assim como futuras opções profissionais e sociais (Morais, Almeida, e Azevedo, 2014). Por seu lado, tem havido debates sobre a especificidade da criatividade, isto é, sobre a sua manifestação ocorrer diferentemente em contextos específicos (Sternberg, Grigorenko, e Singer, 2006), reforçando a investigação atual o predomínio de tal especificidade face às semelhanças da expressão criativa em diferentes domínios (Baer, 2011).…”
unclassified